2015
DOI: 10.1152/jn.00332.2015
|View full text |Cite
|
Sign up to set email alerts
|

Role of the retrotrapezoid nucleus/parafacial respiratory group in coughing and swallowing in guinea pigs

Abstract: The retrotrapezoid/parafacial respiratory group (RTN/pFRG) located ventral to the facial nucleus plays a key role in regulating breathing, especially enhanced expiratory activity during hypercapnic conditions. To clarify the roles of the RTN/pFRG region in evoking coughing, during which reflexive enhanced expiration is produced, and in swallowing, during which the expiratory activity is consistently halted, we recorded extracellular activity from RTN/pFRG neurons during these fictive behaviors in decerebrate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…In addition, an essential role of the cVRG has been suggested in the genesis of the overall cough motor pattern. The results of drug microinjections into the cVRG, along with those obtained by Sugiyama et al (2015) with transverse brainstem sections, suggest that the neuronal network essential for coughing is rather caudal and could mainly involve the cNTS and the neighboring inspiratory and expiratory regions of the ventral respiratory column.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 71%
See 2 more Smart Citations
“…In addition, an essential role of the cVRG has been suggested in the genesis of the overall cough motor pattern. The results of drug microinjections into the cVRG, along with those obtained by Sugiyama et al (2015) with transverse brainstem sections, suggest that the neuronal network essential for coughing is rather caudal and could mainly involve the cNTS and the neighboring inspiratory and expiratory regions of the ventral respiratory column.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 71%
“…Recently, recordings from respiration-related neurons have been performed also in the RTN/pFRG region of the guinea pig during coughing and swallowing (Sugiyama et al, 2015). This structure functions as a chemosensitive center that detects environmental CO 2 and expresses a paired-like homeobox 2b gene (Phox2b).…”
Section: Neuronal Recordings C-fos Immunohistochemistry and Lesion Ementioning
confidence: 99%
See 1 more Smart Citation
“…Experiments were performed on 14 purpose-bred Wistar rats (Shimizu Laboratory Supplies, Kyoto, Japan) of either sex, weighing 40 to 60 g (postnatal days [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. All experimental procedures were conducted according to the principles for the Care and Use of Animals of the Physiological Society in Japan.…”
Section: Methodsmentioning
confidence: 99%
“…As to the RTN/pFRG, the activity of the majority of respiratory neurons in this region was changed in synchrony with coughing and swallowing. However, transverse brainstem sections suggested that the neuronal mechanisms essential for coughing are relatively caudal and could involve mainly the caudal nucleus tractus solitarii (NTS) and neighboring inspiratory and expiratory regions of the ventral respiratory column (Sugiyama et al 2015). In fact, transections caudal to the RTN/pFRG region decreased, but did not abolish cough-related abdominal nerve discharges.…”
Section: Some Characteristics Of the Cvrg (Nra) Neuronsmentioning
confidence: 99%